The economics of urban amenities - Tolley, George S., 1925-; Diamond, Douglas B. (Douglas Byrnne), 1949- (Studies in urban economics., 1982)
The Economics of Urban Amenities discusses amenities through a conceptual, methodological, and empirical basis. The text also defines amenities in a wide variety of human well-being. This collection of papers starts with a review of the concept of amenity. This book contains papers that discuss the economic roles of urban amenities and the resident's site choice. This text also discusses the methods of amenity market analysis including assumptions of hedonic prices and residential location, the exogeneity issues, applications of the limited Box-Cox search, and the Hausman test. Several papers.